Introduction to MPI - Neeman, Henry (My University, 2015)
"Introduction to MPI" (Henry Neeman) LCI Workshop, Mon May 18 2015
Dr. Henry Neeman, University of Oklahoma Assistant Vice President, Information Technology - Research Strategy Advisor Director, OU Supercomputing Center for Education & Research (OSCER) Associate Professor, College of Engineering Adjunct Faculty, School of Computer Scienc
Keywords: Computer Science